Comparative description of the beaks of Chiroteuthis (cf) veranyi Férussac, 1835, Liocranchia reinhardti Steenstrup, 1856, and Doryteuthis opalescens Berry, 1911 paralarvae (Cephalopoda: Teuthoidea) - Santos, Rita Melo Franco (2012)
Orientadora : Profa. Dra. Érica Alves Gonzáles Vidal